Copper and zinc deficiency in an alcoholic patient: a case report of a therapeutic dilemma. Issue 4 (3rd October 2022) - Ito, Hiroshi; Ogawa, Yasuhiro; Shimojo, Nobutake; Kawano, Satoru
Abstract: Copper deficiency often manifests with anemia and ataxia. The risk factors associated with the deficiency include gastrointestinal surgery, excessive zinc supplementation, and malabsorptive conditions. Little is known about the relationship between copper deficiency and alcohol consumption. Here we report a case of copper deficiency in a patient with alcohol use disorder who also had zinc deficiency, thereby posing a therapeutic dilemma because copper and zinc are competitively absorbed into the small intestine. Early recognition of copper deficiency is essential when treating zinc deficiency in such patients.